The Influence of Instructional Syntax to Engage EFL Students in Online Learning Environment - Darmawansah, Darmawansah; Indartono, Setyabudi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This paper aims to analyse the instructional syntax for an online learning environment in English language learning. The data collection used lesson plans in a Spain-based English Academy. The research method used Hemphill’s engagement criteria to find the syntax characteristic in the lesson plans instructions. Also, the study analysed the factors of engagement during the learning session. The study revealed the frequencies of the instructional syntax used by EFL teachers and how these instructions engage the students. The lessons plans were coded to find the most syntax used and the engagement criteria. The result identified ‘ask’ is the most used syntax with 15.3% while inquiries method (38.9%) was using the most in teaching students online. Moreover, the distribution item of engagement factors as EFL online teachers’ focus group discussion shows how the engagement model can be used for English learners. This study will contribute as an expanding method of English language learning in an online setting widely.